Hotel Todo Incluido: Ayllu Urubamba - Manzanal Gambetta, Antonella del Carmen (2023)
After the Covid-19 pandemic, the tourism sector in Peru was very seriously affected (Ministry of Foreign Trade and Tourism, 2020). This led many hotels to close their doors indefinitely without knowing what would come in the future. When tourism was reactivated, at the end of the pandemic, new and innovative tourism proposals emerged that break the mold and challenge tourists to delve into a different type of tourism. During the resolution of the case, we seek to find strategies that appeal to this type of tourist to take advantage of the opportunities that the current tourism market has to offer. After an analysis of the competitive environment, the main target audience was defined as people between 25 and 40 years old from Metropolitan Lima who seek to travel within the country looking for a different type of tourism who are in a socioeconomic level A or A+. Based on these, the brand strategy was carried out in line with their interests and tastes. Thus, with the support of primary sources and analysis of secondary sources, it was possible to put together a 360° launch strategy and proposal that puts the Ayllu Urubamba Hotel in the public eye. This strategy presented the brandbook, and base concept for the brand, a complete brief of the launch event, a strategy with a focus on PR and digital strategy and, finally, a broken down budget.